Urgensi Pengaturan Batas Maksimal dalam Pemberian Insentif Pajak bagi Investor oleh Pemerintah Daerah - Bima Wiyatno; Satrya Harahap; Sherina Gunawan (CV Rewang Rencang, 2025)
Taxes are the primary source of state revenue, serving as a tool for financing development and regulating the economy. Local governments have the authority to provide tax incentives to attract investment; however, without clear regulations, this may potentially reduce regional revenue. This study discusses the urgency of regulating tax incentives and implementing maximum limits to ensure effectiveness, fairness, and support for sustainable development. The findings indicate the need for rules regarding the forms, mechanisms, criteria, and limitations of tax incentives to maintain regional fiscal stability. Proper tax incentive regulation is a key strategy to enhance investment and improve public welfare.